Analysis of consumer satisfaction with digital marketing and service quality - Dede Jajang Suyaman; Cucun Cunayah; Widiarti Widiarti; Moch Fachrizal Nurhanansyah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The phenomenon of technological development is growing rapidly based on digital information system technology in Indonesia today. Some financial products and exchange rates commonly used in electronic payments have now become an unavoidable paradigm in trade or services. Objective This research aims to determine the condition of digital marketing variables, service quality and customer satisfaction at Brits Hotel Karawang. This research is a sample study conducted by consumers as respondents in the research, data collection using a questionnaire with a total of 100 respondents consisting of consumers and visitors to Café and Resto Karawang. The analytical method used is a quantitative method with descriptive analysis and verification analysis. To process the data the author used the help of Microsoft Excel 2016 and SPSS 22 For Windows programs. The results of the research that has been carried out state that digital marketing is at quite good criteria, service quality is at quite good criteria and customer satisfaction is also at quite good criteria. The T test results show that digital marketing partially influences customer satisfaction, service quality partially influences customer satisfaction. The F test results show that digital marketing and service quality simultaneously influence customer satisfaction. To get better customer satisfaction, Brits Hotel Karawang must pay more attention to digital marketing and service quality simultaneously. Because these two variables play an important role in customer satisfaction. This implication reflects the need for organizations to continue to adapt to technological trends and focus on developing these aspects to win competition in an increasingly digital market. Additionally, the findings of this research also underscore the importance of understanding customer perceptions and preferences in the context of digital marketing to improve their impact on overall customer satisfaction.